2015
DOI: 10.1016/j.mayocp.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Blockers of Angiotensin Other Than Olmesartan in Patients With Villous Atrophy: A Nationwide Case-Control Study

Abstract: Objective To examine the association between previous use of non-olmesartan angiotensin receptor blockers (ARBs) or any angiotensin-converting enzyme inhibitors (ACEIs) in patients with small-intestinal villous atrophy (VA) as compared with general population matched controls. Patients and methods A case-control study was used to link nationwide histopathology data on 2933 individuals with VA (Marsh grade 3) to the Swedish Prescribed Drug Register to examine the association between use of ACEIs as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(42 reference statements)
0
12
1
1
Order By: Relevance
“…Olmesartan can cause a severe sprue‐like enteropathy that mimics coeliac disease histologically, and which improves following medication cessation . There are case reports of similar occurrences with other members of the angiotensin receptor antagonist class; however, this has not been demonstrated in larger studies . In our study, angiotensin receptor antagonist use was not associated with impaired mucosal healing in this study; however, the overall prevalence of use was too low to detect an effect size of a similar magnitude to that seen for NSAIDs and PPIs.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Olmesartan can cause a severe sprue‐like enteropathy that mimics coeliac disease histologically, and which improves following medication cessation . There are case reports of similar occurrences with other members of the angiotensin receptor antagonist class; however, this has not been demonstrated in larger studies . In our study, angiotensin receptor antagonist use was not associated with impaired mucosal healing in this study; however, the overall prevalence of use was too low to detect an effect size of a similar magnitude to that seen for NSAIDs and PPIs.…”
Section: Discussioncontrasting
confidence: 60%
“…The relevance of other types of symptoms on risk of persistent villus atrophy has not, however, been studied. Drug‐induced enteropathy is well recognised and has been linked to use of angiotensin‐receptor blockers, non‐steroidal anti‐inflammatory drugs (NSAIDs), and possibly proton‐pump inhibitors (PPIs), however the impact of use of these medications on healing of villus atrophy in coeliac disease is not known …”
Section: Introductionmentioning
confidence: 99%
“…A third study did not find an increased risk of intestinal malabsorption with olmesartan compared with other ARBcor ACE inhibitors in admitted patients in Germany and Italy, however it did not assess risk as a function of duration of therapy, there were limited number of events and 95% confidence intervals between groups were wide and overlapping. There is further support from Sweden, where olmesartan is not available, that this is a particular risk with olmesartan, rather than a class effect of ARB. A case–control study of 2933 histologically confirmed cases of villous atrophy, did not find an association between use of ACE inhibitors or non‐olmesartan ARB, suggesting that these medications are not a major risk factor for the development of villous atrophy in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Olmesartan-induced selective AT1 receptor blockade also results in a translocation of AT2 receptors to the outer part of the basolateral cell membrane. [14,15] This receptor translocation favors the binding of angiotensin II to AT2 receptors, possibly resulting in the pro-apoptotic effect seen in OAE. The duodenal-jejunal histology is characterized by villous atrophy and increased intra-epithelial lymphocytes (CD3 and CD8 lymphocytes) apparently due to apoptosis of enterocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested an association between use of olmesartan and a sprue-like enteropathy, with affected patients presenting with severe, protracted diarrhea and weight loss that improves after discontinuation of olmesartan. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although the symptoms and histologic findings of olmesartan-associated enteropathy (OAE) resemble severe celiac disease, negative laboratory testing for celiac disease and lack of a response to a gluten-free diet suggest that OAE is a separate clinical entity. The pathogenesis of this entity remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%